Pengaruh Injeksi Larutan Gula Lontar Cair Terhadap Pertumbuhan Diameter Ranting Kesambi (Schleichera oleosa) Sebagai Inang Kutu Lak (Laccifer lacca) - Faustinus Kadha; Supriyanto Supriyanto; N F Haneda (Savana Cendana, 2023)
The Laccifer lacca lives parasitically on kesambi (Schleichera oleosa) which has branches that are not too old or not too young and are gray-green in color. The Laccifer lacca sticks its proboscis into the branch and reaches the phloem tissue. Kesambi that lacks phloem fluid will cause decreased growth, yellow leaves and fall off. The purpose of this study was to inject liquid palm sugar solution into kesambi plant tissue by using an injection pump technique or a multi-injection technique. This research was carried out through the process of injecting kesambi, inoculation of Laccifer lacca, maintenance, and measuring the growth of branch diameter. The diameter of the branch where the Laccifer lacca live can be divided into 3 sizes, namely large (> 0.74 cm), medium (0.50–0.74 cm), and small (< 0.50 cm). The growth of branch diameter did not show a significant difference of 0.3 cm/5 months of observation at all concentrations of LGCL.